Mixed infections by different Trypanosoma cruzi discrete typing units among Chagas disease patients in an endemic community in Panama - Ledezma, Alexa Prescilla (2020)
Background Trypanosoma cruzi, the hemoparasite that causes Chagas disease, is divided into six Discrete Typing Units or DTUs: TcI-TcVI plus Tcbat. This genetic diversity is based on ecobiological and clinical characteristics associated with particular populations of the parasite. The main objective of this study was the identification of DTUs in patients with chronic chagasic infections from a mountainous rural community in the eastern region of Panama. Methods A total of 106 patients were tested for Chagas disease with three serological tests (ELISA, rapid test, and Western blot). Molecular diagnosis and DTU typing were carried out by conventional PCRs and qPCR targeting different genomic markers, respectively. As a control sample for the typing, 28 patients suspected to be chagasic from the metropolitan area of Panama City were included. Results showed a positivity in the evaluated patients of 42.3% (33/78); high compared to other endemic regions in the country. In the control group, 20/28 (71.43%) patients presented positive serology. The typing of samples from rural patients showed that 78.78% (26/33) corresponded to TcI, while 9.09% (3/33) were mixed infections (TcI plus TcII/V/VI). Seventy-five percent (15/20) of the patients in the control group presented TcI, and in five samples it was not possible to typify the T. cruzi genotype involved. Conclusions These results confirm that TcI is the main DTU of T. cruzi present in chronic chagasic patients from Panama. However, the circulation of other genotypes (TcII/V/VI) in this country is described for the first time. The eco-epidemiological characteristics that condition the circulation of TcII/V/VI, as well as the immune and clinical impact of mixed infections in this remote mountainous region should be investigated, which will help local action programs in the surveillance, prevention, and management of Chagas disease.